Psychosis After Mild Traumatic Brain Injury and the Role of an Integrated Brain Medicine Clinic - Carl Froilan D. Leochico; Adrian I. Espiritu; Sarah E. Levitt; Sabrina Lemire-Rodger; Meiqi Guo; Sara B. Mitchell (Case Reports in Psychiatry)
Psychosis after mild traumatic brain injury (TBI) can be rare, complex, and functionally impairing, often requiring inputs from various specialties. This usually entails separate visits and long wait times. We present the case of an elderly patient with schizophrenia-like psychosis after a mild TBI. Three years after the TBI, the treating physiatrist requested diagnostic clarifications and treatment recommendations from a brain medicine clinic (BMC), a novel integrated virtual clinic composed of neurology, psychiatry, and other brain-related disciplines. Six months later, the patient was overall improved, and her driver’s license, which had been suspended 6 months after the TBI, was reinstated. We discuss diagnostic and treatment challenges of TBI. BMCs could provide timely, comprehensive, and efficient access to multispecialty care and resources for patients with complex brain disorders and minimize the artificial siloes in healthcare.